Patients with Ulcerative Colitis Are More Concerned About Complications of Their Disease than Side Effects of Medications. Issue 4 (April 2016) - Thompson, Kimberly D.; Connor, Susan J.; Walls, Danielle M.; Gollins, Jan; Stewart, Sabrina K.; Bewtra, Meena; Baumblatt, Geri L.; Holubar, Stefan D.; Greenup, Astrid-Jane; Sechi, Alexandra; Girgis, Afaf; Rubin, David T.; et al.
Abstract : Background: Patients with ulcerative colitis (UC) are often fearful about medication side effects and how the disease will affect their future. Our aim was to better understand what aspects of UC, and UC management, are most concerning to patients, and how they would like to be informed about treatment options. Methods: A Web-based survey was sent to UC patients throughout the United States and Australia. In addition to standard closed-response questions, audio clips were embedded in the survey and respondents showed their strength of agreement or disagreement using moment-to-moment affect-trace methodology. Standard quantitative analysis was used for the survey results, and cluster analysis was performed on the affect-trace responses. Results: A total of 460 patients with UC (370 patients from the United States and 90 patients from Australia) responded to the survey. Of them, 53% of the respondents were women, with a mean age of 49 (range 19–81) years. Most patients (87%) wanted to share treatment decision making with their doctors. The majority, 98%, wanted more than just a basic understanding of their disease. Patients were most concerned about the risk of colorectal cancer (37%), and the possible need for an ileostomy (29%). Only 14% of patients indicated that side effects from medications were their biggest concern. On affect-trace analysis, the most divergence in opinion centered on the appropriate timing for colectomy. Conclusions: To facilitate informed treatment decisions for UC patients, in addition to reviewing the benefits and risks of medications, it is also important to discuss the best strategies for decreasing the risk of colectomy and colorectal cancer. Abstract : Article first published online 7 March 2016.